2017
DOI: 10.1016/j.prostaglandins.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mitochondrial dysfunction and endoplasmic reticulum stress are key mechanisms for the wide-ranging actions of epoxy fatty acids and soluble epoxide hydrolase inhibitors

Abstract: The arachidonic acid cascade is arguably the most widely known biologic regulatory pathway. Decades after the seminal discoveries involving its cyclooxygenase and lipoxygenase branches, studies of this cascade remain an active area of research. The third and less widely known branch, the cytochrome P450 pathway leads to highly active oxygenated lipid mediators, epoxy fatty acids (EpFAs) and hydroxyeicosatetraenoic acids (HETEs), which are of similar potency to prostanoids and leukotrienes. Unlike the COX and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 142 publications
5
75
0
Order By: Relevance
“…After MIA. It is reported that the sEH inhibitor attenuates activation of the ER (26,(42)(43)(44). In this study, we examined the effects of TPPU on ER stress in the brain regions from juvenile offspring after MIA.…”
Section: Role Of Seh In Er Stress In the Mouse Brain From Juvenile Ofmentioning
confidence: 98%
“…After MIA. It is reported that the sEH inhibitor attenuates activation of the ER (26,(42)(43)(44). In this study, we examined the effects of TPPU on ER stress in the brain regions from juvenile offspring after MIA.…”
Section: Role Of Seh In Er Stress In the Mouse Brain From Juvenile Ofmentioning
confidence: 98%
“…EETs also activate nuclear erythroid-related factor 2 (Nrf2), which induces the expression of antioxidant proteins and enzymes. At the cellular level, EETs are postulated to maintain ER-mitochondria homeostasis and limit reactive oxygen species formation by modulating the ER stress response and maintaining mitochondrial function (Inceoglu et al, 2017). …”
Section: Recently Identified Molecular/cellular Targets and Approachesmentioning
confidence: 99%
“…Its expression may be enhanced by different cellular stresses, including ER stress, thereby attenuating EETs’ protective actions (Inceoglu et al, 2017; Inceoglu et al, 2015; Mak et al, 2017). Accumulating evidence has shown that salubrinal, an agent that limits ER stress by enhancing the unfolded protein response, has protective effects on the BBB in ischemic stroke by blocking the progression of the inflammatory response that is linked to microglial reactivity and production of MMP9 (Anuncibay-Soto et al, 2018).…”
Section: Recently Identified Molecular/cellular Targets and Approachesmentioning
confidence: 99%
“…It is known that the ER stress plays a role in the pathogenesis of neurodegenerative disease, including AD (33), and those sEH inhibitors attenuate activation of the ER stress response (10). Therefore, we measured the levels of the ER stress sensors ATF-6 and IRE1α (Fig.…”
Section: Seh Inhibitors Reduce Biomarkers Of Inflammation Oxidation mentioning
confidence: 99%
“…Epoxyeicosatrienoic acids (EETs) mediate vasodilatation, reduce inflammation, attenuate OS and block the pathological endoplasmic reticulum (ER) stress response (10,11). The soluble epoxide hydrolase enzyme (sEH, EC 3.3.2.10, EPHX2), widely expressed in relatively high abundance in the murine and human brains (12,13), converts EETs and other epoxyfatty acids (EpFA) to their corresponding dihydroxyeicosatrienoic acids (DHETs), whereby diminishing, eliminating, or altering the beneficial effects of EETs (14) (Fig.…”
Section: Introductionmentioning
confidence: 99%